Pengaruh electronic-Word of Mouth (e-WOM) dan Content Marketing Terhadap Impulse Buying Mahasiswa Uniga Pada Produk Jiniso di TikTokshop - Rismanto Hilman; Maharani Mira; Mulyani Yani; Sarah Siti; Padillah Eva (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the influence of electronic word of mouth (e-WOM) and content marketing on impulse buying behavior of Jiniso products among Universitas Garut students who use TikTok Shop. The rapid growth of social commerce has encouraged consumers, particularly Generation Z, to rely on online reviews and engaging digital content, which may trigger unplanned purchasing decisions. This research adopts a quantitative approach by collecting primary data through questionnaires distributed to students who have made purchases on TikTok Shop. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships among variables. The results indicate that both e-WOM and content marketing have a positive and significant effect on impulse buying. e-WOM shows a stronger influence, suggesting that online reviews, recommendations, and shared experiences play a crucial role in shaping consumer trust and emotional responses that lead to spontaneous purchases. Meanwhile, attractive, informative, and relevant marketing content also significantly stimulates consumers’ interest and purchasing impulses. These findings imply that businesses, especially fashion brands on social commerce platforms, should optimize user-generated reviews and develop creative content strategies to enhance consumer engagement and increase impulsive purchase behavior.